Analysis of Fan Engagement and Community Building: A Case Study of MPL Indonesia Season 12 - Mamanua, Samuel Edson Billy (Innovative: Journal Of Social Science Research, 2024)
This study delves into the multifaceted landscape of fan engagement and community dynamics within the Mobile Legends: Bang Bang Professional League (MPL) Indonesia focusing on its Season 12. Drawing from participants’ responses, this study unveils a fervent fan base with high engagement ratings and diverse team affiliations rooted in personal connections and team performance. While the sense of community among MPL fans is perceived as moderate, participants advocate for augmented community-building initiatives, emphasizing the potential of offline events to forge stronger bonds. Communication channels primarily encompass social media and in-game chats, yet concerns surrounding toxic behavior loom large. Factors contributing to toxicity include intense competition and online anonymity, damaging the fan experience. Mitigation strategies proposed include stricter penalties, education, and promoting respectful communication. Ultimately, this study underscores the need for a proactive, multi-pronged approach to enhance fan engagement, foster community unity, and combat toxicity within esports communities.